Project management achieving competitive advantage - Pinto, Jeffrey K. (Pearson Education Limited, 2013)
For courses in project management. The fundamentals of project management with a wide assortment of business applications. Project Management takes a decision-making, business-oriented approach to the management of projects, which is reinforced throughout the text with current examples of project management in action. And because understanding project management is central to operations in various industries, this text also addresses project management within the context of a variety of successful organizations, whether publicly held, private, or not-for-profit